2021
DOI: 10.47672/jsm.669
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Management Practices and Performance of Health Non-Governmental Organizations in Nairobi City County, Kenya

Abstract: Introduction: The contemporary business environment in which organizations operate is increasingly becoming uncertain and unpredictable, and it has been established that little is known of the implementation of strategic planning practices among not-for-profit organizations in developing countries, despite increased inability to meet estimated project timelines, quality and budget allocation. Purpose: This study aimed to examine how strategic management practices influence health NGOs' performance in Nai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…Thus, PSC performance was improved by using appropriate inventory level control methods such as batch control and stock review and having suitable replenishment decisions such as lead time management. This finding is consistent with the findings of previous studies (Fredrick, 2018; Odhiambo & Kihara, 2018; Rachmania & Basri, 2013). The results suggest that hospital pharmacies need to implement appropriate inventory management practices to ensure zero stockouts and withstand fluctuations in demand and supply.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Thus, PSC performance was improved by using appropriate inventory level control methods such as batch control and stock review and having suitable replenishment decisions such as lead time management. This finding is consistent with the findings of previous studies (Fredrick, 2018; Odhiambo & Kihara, 2018; Rachmania & Basri, 2013). The results suggest that hospital pharmacies need to implement appropriate inventory management practices to ensure zero stockouts and withstand fluctuations in demand and supply.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, the hospital pharmacy management teams should implement inventory management practices to improve the hospital's performance. Also, Odhiambo and Kihara (2018) investigated the effect of inventory management practices on the SC performance of government health facilities in Kenya. This study assessed inventory management in terms of four practices, namely: lean inventory practices, inventory records accuracy, information technology, and demand forecasting.…”
Section: The Relationship Between Inventory Level Control and Pharmac...mentioning
confidence: 99%
“…The findings concur with those by Waribu (2019) who established that strategic direction setting has a significant influence on firm competitiveness. A study by Odhiambo (2020) revealed that when strategic leaders set the right strategic direction for the organization through aligned vision and mission, they strongly and positively influence organization's continued competitive advantage.…”
Section: Resultsmentioning
confidence: 99%
“…While some of the project that are initiated get to be completed in a timely manner and according to specification some others experience either delays, don't get to be completed at all or if completed fall below standard. Also Odhiambo and Njuguna (2021) reported that Kenyan NGOs deal with a number of management issues, including those related to budgeting, hiring, and overall operational administration of the organization. Effectively managing connections with other parties, such as those with businesses, government agencies, non-profits, and the communities they serve, is another problem they encounter and these challenges significantly impacts their project performance.…”
Section: Statement Of the Problemmentioning
confidence: 99%